Preservice English Language Teacher Education in the Anthropocene - Ahmet Erdost Yastiba? (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
The new geological epoch, the Anthropocene reveals the negative impacts of human activities on the environment, which makes environmental education significant to deal with the negative effects of people on the environment and sustain the environment for the future of the world. As a branch of education, English language teaching (ELT) can contribute to environmental education in schools. For an effective environmental education in ELT, English language teachers should have enough knowledge on environmental issues and environmental awareness. One way for them to achieve this is preservice English language teacher education. The literature review indicated that any English language teacher education program (ELTEP) was not evaluated with an anthropocentric perspective. Therefore, the present study aimed to evaluate the new ELTEP of Turkey with an anthropocentric perspective. It was designed as a qualitative study. The data was collected from the new ELTEP of Turkey and was content analyzed. The findings of the study have shown that environmental education is integrated with the new ELTEP through community services and sustainable development and education courses. The findings of the study were discussed and suggestions for further studies were made.